A closer look into the microbiome of microalgal cultures - Steinrücken, Pia; Jackson, Steve; Müller, Oliver; Puntervoll, Pål; Kleinegris, Dorinde M. M. (Frontiers in Microbiology, 2023)
Although bacteria are commonly co-occurring in microalgal cultivation and production systems, little is known about their community structure and how it might be affected by specific microalgal groups or growths conditions. A better understanding about the underlying factors that determine the growth of specific bacterial populations is not only important for optimizing microalgal production processes, but also in the context of product quality when the algal biomass is to be used for future food or feed. We analyzed the bacterial community composition associated to nine microalgal strains in stock culture, maintained in two different growth media, to explore how specific taxonomic microalgal groups, microalgal origin or the growth medium affect the bacterial community composition. Furthermore, we monitored the bacterial community composition for three Phaeodactylum strains during batch cultivation in bubble columns to examine if the bacterial composition alters during cultivation. Our results reveal that different microalgal genera, kept at the same cultivation conditions over many years, displayed separate and unique bacterial communities, and that different strains of the same genus had very similar bacterial community compositions, despite originating from different habitats. However, when maintained in a different growth medium, the bacterial composition changed for some. During batch cultivation the bacterial community structure remained relatively stable for each Phaeodactylum strain. This indicates that microalgae seem to impact the development of the associated bacterial communities and that different microalgal genera could create distinct conditions that select for dominance of specific bacteria. However, other factors such as the composition of growth medium also affect the formation of the bacterial community structure.